Ultrasound dynamics of gastric content volumes after the ingestion of coconut water or a meat sandwich. A randomized controlled crossover study in healthy volunteers - Carmona, Bruno Mendes; Almeida, Clauber Claudino Alves; Vieira, Waldônio De Brito; Fascio, Mario De Nazareth Chaves; Carvalho, Lídia Raquel De; Vane, Luiz Antonio; Barbosa, Fabiano Timbó; Nascimento Junior, Paulo Do; Módolo, Norma Sueli Pinheiro (Sociedade Brasileira de Anestesiologia, 2018)
AbstractBackground: Adequate preoperative fasting is critical in preventing pulmonary aspiration of gastric content. We proposed to study the sonographic gastric content dynamics after the ingestion of liquid or solid food in healthy volunteers and confront it with current guidelines for preoperative fasting times.Methods: We performed a prospective, crossover, evaluator-blinded study involving 17 healthy volunteers of both sexes. Each participant fasted for 10 h and was subjected to a baseline gastric ultrasound, intake of 400 mL of coconut water or a 145 g, 355 kcal meat sandwich, and sonographic gastric evaluations after 10 min and every hour until the stomach was completely empty.Results: At baseline, all subjects had an empty stomach. At 10 min, gastric content [mean + standard deviation (SD)] was 240.4 + 69.3 and 248.2 + 119.2 mL for liquid and solid foods, respectively (p > 0.05). Mean + SD gastric emptying times were 2.5 + 0.7 and 4.5 + 0.9 h for liquid and solid foods, respectively (p < 0.001). For the drink, the stomach was completely empty in 59% and 100% of the subjects after two and four hours, and for the sandwich, 65% and 100% of the subjects after four and seven hours, respectively.Conclusions: Sonographic gastric dynamics for coconut water and a meat sandwich resulted in complete gastric emptying times higher and lower, respectively, than those suggested by current guidelines for preoperative fasting.

ResumoJustificativa: O jejum pré-operatório adequado é fundamental para prevenir a aspiração pulmonar do conteúdo gástrico. Nossa proposta foi avaliar a dinâmica ultrassonográfica do conteúdo gástrico após a ingestão de alimentos líquidos ou sólidos em voluntários sadios e confrontá-la com as diretrizes atuais para os períodos de jejum no pré-operatório.Métodos: Um estudo prospectivo, cruzado e avaliador-cego foi feito com 17 voluntários saudáveis de ambos os sexos. Cada participante jejuou por 10 horas e foi submetido a uma ultrassonografia gástrica na fase basal, ingestão de 400 mL de água de coco ou 355 g de sanduíche de carne e avaliações gástricas ultrassonográficas foram feitas após 10 minutos e a cada hora até o estômago estar completamente vazio.Resultados: Na fase basal, todos os participantes estavam com o estômago vazio. Aos 10 minutos, o conteúdo gástrico [média + desvio-padrão (DP)] foi de 240,4 + 69,3 e 248,2 + 119,2 mL para alimentos líquidos e sólidos, respectivamente (p > 0,05). Os tempos médios de esvaziamento gástrico + DP foram de 2,5 + 0,7 e 4,5 + 0,9 horas para alimentos líquidos e sólidos, respectivamente (p < 0,001). Para a bebida, o estômago ficou completamente vazio em 59% e 100% dos sujeitos após duas e quatro horas; para o sanduíche, o estômago ficou completamente vazio em 65% e 100% dos sujeitos após quatro e sete horas, respectivamente.Conclusões: A dinâmica ultrassonográfica do volume gástrico para água de coco e sanduíche de carne resultou em tempos totais de esvaziamento gástrico maiores e menores, respectivamente, do que os sugeridos pelas diretrizes atuais para o jejum pré-operatório.
Dinâmica ultrassonográfica dos volumes do conteúdo gástrico após a ingestão de água de coco ou sanduíche de carne. Um estudo cruzado controlado e randômico com voluntários saudáveis
Keywords: Ultrasound; Gastric content; Gastric dynamics; Preoperative fasting; Ultrassom; Conteúdo gástrico; Dinâmica gástrica; Jejum pré-operatório